2018
DOI: 10.1038/s41598-018-23221-9
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and optical properties of epitaxial binary and ternary GeTe-Sb2Te3 alloys

Abstract: Phase change materials such as pseudobinary GeTe-Sb2Te3 (GST) alloys are an essential part of existing and emerging technologies. Here, we investigate the electrical and optical properties of epitaxial phase change materials: α-GeTe, Ge2Sb2Te5 (GST225), and Sb2Te3. Temperature-dependent Hall measurements reveal a reduction of the hole concentration with increasing temperature in Sb2Te3 that is attributed to lattice expansion, resulting in a non-linear increase of the resistivity that is also observed in GST225… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…1 a, the plasma frequency ω p,D controls the total transmittance value and Γ D the transmittance slope increase over the considered bandwidth. At room temperature, the value of ω p,D / 2π = 7,305 cm −1 is remarkably close to the value determined from Hall effect data 19 in bulk material. Moreover, ω p,D is related to the free carrier concentration and their effective mass m * via .…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…1 a, the plasma frequency ω p,D controls the total transmittance value and Γ D the transmittance slope increase over the considered bandwidth. At room temperature, the value of ω p,D / 2π = 7,305 cm −1 is remarkably close to the value determined from Hall effect data 19 in bulk material. Moreover, ω p,D is related to the free carrier concentration and their effective mass m * via .…”
Section: Resultssupporting
confidence: 83%
“…Moreover, recent density functional theory (DFT) calculations show that the band gap of Sb 2 Te 3 increases with increasing temperature due to the thermal expansion of Sb 2 Te 3 18 and such raise of the bandgap would result in a reduction of the free carrier concentration. Experimental verification of the theory can be found in Boschker et al 19 .
Figure 1 (a) Temperature dependent THz transmittance change of Sb 2 Te 3 .
…”
Section: Resultsmentioning
confidence: 87%
“…Hall measurements revealed that GeTe films are intrinsically p-type doped (p ≈ 2 × 10 20 cm −3 -a typical concentration for this material 35 ) due to the presence of about 10% Ge vacancies 48 . The mobility at room temperature 50 is 95 cm 2 V −1 s −1 .…”
Section: Methodsmentioning
confidence: 99%
“…The crystallization temperature for GeTe is ≈ 180 • C (453 K) [9,10]. GeTe has also been implemented with a superlattice configuration as GeTe-Sb 2 Te 3 that are extensively used for their application in optical as well as PCM storage devices [11]. Further, the interface between the GeTe and Sb 2 Te 3 in the superlattice configuration is found to control the phase transition, accompanied by a reduced entropy loss, which helps in making fast and efficient PCMs [12].…”
Section: Introductionmentioning
confidence: 99%